Curriculum Based on Religious Values Evaluation Criteria for Religious Based Curriculum in Educational - Sudarji; Muhamad Sidiq Asyhari (Khazanah: Journal of Islamic Education and Science, 2026)
Curriculum is the core of the educational system that plays an important role in instilling religious values and shaping students’ character. Amid technological developments and social changes, the implementation of a religious values-based curriculum needs to be evaluated to remain relevant to modern educational demands. Previous studies have mainly focused on curriculum design and learning outcomes, while comprehensive evaluations of the implementation of religious values-based curricula remain limited. This study aims to evaluate curriculum implementation using the CIPP (Context, Input, Process, Product) model through a qualitative approach involving interviews, observations, and document analysis. The findings indicate that the curriculum has been designed to integrate religious values into learning activities and school culture; however, its implementation still faces challenges related to teachers’ pedagogical competence, the use of technology, and the consistency of applying religious values. In addition, students demonstrate good religious understanding, although character strengthening and adaptation to technological developments still need improvement.